2020
DOI: 10.3390/su12187642
|View full text |Cite
|
Sign up to set email alerts
|

The Right Time for Crowd Communication during Campaigns for Sustainable Success of Crowdfunding: Evidence from Kickstarter Platform

Abstract: Only a small percentage of crowdfunding projects succeed in securing funds, the fact of which puts the sustainability of crowdfunding platforms at risk. Researchers have examined the influences of phased aspects of communication, drawn from updates and comments, on success of crowdfunding campaigns, but in most cases they have focused on the combined effects of the aspects. This paper investigated campaign success contribution of various combinations of phased communication aspects from updates and comments, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 66 publications
1
13
0
2
Order By: Relevance
“…A total of 24 publicly available campaigns, mostly from the platforms Kickstarter (www.kickstarter.com (accessed on 15 January 2021); Ryoba et al 2020) and IndieGogo (www.indiegogo.com (accessed on 15 January 2021); Maryani and Udiono 2020), with a funding volume of more than 5 million USD were taken into consideration. The connection between crowdfunding and retail shall be highlighted and discussed in this manner.…”
Section: Research Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A total of 24 publicly available campaigns, mostly from the platforms Kickstarter (www.kickstarter.com (accessed on 15 January 2021); Ryoba et al 2020) and IndieGogo (www.indiegogo.com (accessed on 15 January 2021); Maryani and Udiono 2020), with a funding volume of more than 5 million USD were taken into consideration. The connection between crowdfunding and retail shall be highlighted and discussed in this manner.…”
Section: Research Resultsmentioning
confidence: 99%
“…It contributes to the discussion with the empirically based development of a theoretical framework and provides another example of how the grounded theory approach can be applied. The research done shows that crowdfunding for products and services, apart from the economic perspective, is tied to the idea of sustainability, given the feedback of the supporters, the close but open communication with the crowd, as well as the included willingness for change and adaptation by the campaign owners (Moritz et al 2015;Ryoba et al 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Besides, Stegmaier [39] (p. 45) indicates that three updates per week are ideal and beyond that is possibly too much. Ryoba et al [64] suggest a phased approach to communication where the number of updates needs to be the first priority in the beginning while later stages require polarity of comments and readability of updates becoming increasingly important. We, therefore, find overall that comments and updates, although they both are aspects of community engagement and in a sense are two sides of an ongoing conversation, play different roles that warrant additional research.…”
Section: Discussionmentioning
confidence: 99%
“…As stated by Belleflamme et al [ 35 ], a more extensive network of connections is significantly connected with unobservable project quality components; therefore, it serves as a signal. Several scholars [ 15 , 24 , 30 , 36 , 60 , 61 ] found that fundraisers who provide greater awareness through social interactions are considered an attribute of the effectiveness of the signal and predictors of campaign success.…”
Section: Literature Reviewmentioning
confidence: 99%